Agricultural and food policy - Knutson, Ronald D. (Prentice Hall, 1998)
The book introduces economic principles to analyze a particular problem, policy, program, or consequence. The fourth edition of Agricultural and Food Policy has been revised to include comprehensive treatment of international trade policy and the issues likely to dominate the next round of trade negotiations beginning in 2000; policies relating to food safety; the implications of welfare reform on the future scope and structure of the USDA; and current perspectives on the balance of world food supply and demand. The book also includes a new chapter on the ways in which the 1996 Farm bill changes the role of government in agriculture. An essential reference for anyone involved in agriculture or in the formulation of agriculture and food policy